Strategi Pengembangan Potensi Usaha Mikro, Kecil, dan Menengah Kerajinan Tangan Kiso “Jago Abadi” Di Desa Kemiri, Kabupaten Banyumas - Muflih Nurriza Pahlawi; Abu Dharin (BANTENESE : JURNAL PENGABDIAN MASYARAKAT, 2021)
Small and Medium Enterprises (MSMEs) are an inseparable part of the national business world. The existence of MSMEs is something that is quite vital in improving the economy of the Indonesian people in various regions. This study aims to analyze the development strategy of the Kiso "Jago Abadi" handicraft SMEs in Kemiri Village, Banyumas Regency. This study uses qualitative research methods that involve researchers in their research subjects, then participatively identify problems and design empowerment models for development in the form of work programs that can be done. The strategy applied is to design the programs needed for MSMEs as capital for strengthening and knowledge for MSME actors who are involved in it. The way that can be applied is to continue to develop the uniqueness of handicraft products, expand market reach, always maintain and improve product quality, and consistently promote and maintain the production of Kiso "Jago Abadi" handicrafts. The results of this study are the finding of more optimal and efficient results in the production and marketing process of Kiso "Jago Abadi" handicrafts. The strategy for developing the potential of micro, small, and medium-sized handicrafts Kiso "Jago Abadi" in Kemiri village, Banyumas district can achieve maximum results. The results of this study are the finding of more optimal and efficient results in the production and marketing process of Kiso "Jago Abadi" handicrafts. The strategy for developing the potential of micro, small, and medium-sized handicrafts Kiso "Jago Abadi" in Kemiri village, Banyumas district can achieve maximum results. The results of this study are the finding of more optimal and efficient results in the production and marketing process of Kiso "Jago Abadi" handicrafts. The strategy for developing the potential of micro, small, and medium-sized handicrafts Kiso "Jago Abadi" in Kemiri village, Banyumas district can achieve maximum results.